2K/UV dual-curable acrylate epoxy/SiO2 nanocomposite coatings: crosslinking and mechanical properties - Nguyen Ngoc Linh,; Dang Thi My Linh,; Nguyen Tuan Anh,; Vu Quoc Trung,; Nguyen Thien Vuong, (Vietnam Journal of Science and Technology, 2024)
This work aimed to enhance the adhesion of photocurable acrylate epoxy/SiO2 nanocomposite coating by adding a crosslinking agent polyisocyanate Desmodur N75 (N75) to make a 2K/UV dual-curable paint formulation. The obtained results showed that the presence of the curing agent N75 slightly reduced the conversion efficiency of acrylate groups during the UV curing process. The analysis of mechanical properties indicated that the coating achieved the optimal mechanical properties at the N75 content of 5 wt.%. The gel fraction, swelling degree, adhesion to wood and steel, relative hardness, impact resistance, and abrasion resistance reached 97.22 %, 310.05 %, 0.1, 0.94, 90 Kg.cm, and 178 L/mil, respectively. FESEM analysis showed that the paint film was fairly homogeneous and tightly structured. The reactions of components of BGDM, HDDA, I184, N75 and nano-SiO2 in the 2K/UV dual-curable acrylate epoxy/SiO2 nanocomposite coatings were described.